Identification of novel protein tyrosine phosphatase sigma inhibitors promoting neurite extension. Issue 1 (1st January 2016) - Lee, Hye Seon; Ku, Bonsu; Park, Tae Hyun; Park, Hwangseo; Choi, Joong-Kwon; Chang, Kyu-Tae; Kim, Cheol-Hee; Ryu, Seong Eon; Kim, Seung Jun
Graphical abstract: Abstract: Protein tyrosine phosphatase sigma (PTPσ) is a potential target for the therapeutic treatment of neurological deficits associated with impaired neuronal recovery, as this protein is the receptor for chondroitin sulfate proteoglycan (CSPG), which is known to inhibit neuronal regeneration. Through a high-throughput screening approach started from 6400 representative compounds in the Korea Chemical Bank chemical library, we identified 11 novel PTPσ inhibitors that can be classified as flavonoid derivatives or analogs, with IC50 values ranging from 0.5 to 17.5 μM. Biochemical assays and structure-based active site-docking simulation indicate that our inhibitors are accommodated at the catalytic active site of PTPσ as surrogates for the phosphotyrosine group. Treatments of these compounds on PC-12 neuronal cells led to the recovery of neurite extension attenuated by CSPG treatment, demonstrating their potential as antineurodegenerative agents.